Otimização de rotas com o auxilio de uma plataforma SIG-T, no Serviço de Atendimento Móvel de Urgência - SAMU/ João Pessoa /PB - Carvalho Neto, João Filadelfo de (2008)
The accidents and the violence in the urban way result of the actions and or human omissions, through conditioning technical and or society. In 2005, those occurrences were responsible for about 75% of the total of the deaths for violent causes according to ministry of Health of Brazil. A key element in the attendance to the victims of violence and accidents is the time of displacement, that can change the medical picture in subject of minutes, and to do the difference between to survive or to die, according to the procedures of the adopted during the golden hour. In Brazil, a service that has great importance in this activity it is SAMU - Service of Movable Attendance of Urgency and Emergency, in which the choice of the route to be followed by the ambulance, depends in the great majority of the times of the driver's knowledge on the city and of your intuition on the best road to be proceeded, which a lot of times don't represent the fastest. In this perspective, a route tool associated to the use of a Geographical Information System (GIS) was tested gone back to Transports (of the type SIGT), related to the Global Positioning System (GPS), to potency the choice of the best route and the decrease of the time, of the morbimortalidade risk and of the costs generated in the installment of the service. In this work, it was tested in an initial way the viability of use of a tool of to optimize of routes and time of operation in SAMU, through modeling procedures in transports, previously tends as application cell an area chosen in João Pessoa - Paraíba.